Tayma, Saudi-Arabien: Rettungsgrabungen im Gräberfeld von al-Nasim - Hausleiter, Arnulf (e-Forschungsberichte des DAI, 2023)
Saudi-German salvage excavations in the cemetery of al-Nasim, located south of the walled area of the oasis of Tayma, revealed further evidence of early 2nd millennium BC occupation at the site. In addition to characteristic circular graves with pottery findings (Red Burnished Ware/RBW), bronze weapons, such as fenestrated axes and a spear head, indicate close connections between North West Arabia and Syria/the Levant, thus confirming the regional significance of Tayma already during the Middle Bronze Age.